Management of the Nkomati Mine Crusher Slope Failure - R. Armstrong (The Southern African Institute of Mining and Metallurgy, 2014)
Due to limited available level ground, Nkomati Nickel Mine cut a weathered rock slope at the base of a mountain spur in order to create a platform for construction of the primary crusher plant and run-of-mine stockpiles. As space is limited around the mining area, ore processing at Nkomati is based on a high reliability of flow of material through the crusher plant, with minimal usage of other and larger designed stockpiles. Evidently, any crusher plant shutdown will render the mine as a whole unproductive and put excessive strain on the medium- to long-term large ore stockpiles, the deposition rates for which are restricted by founding material consolidation requirements. At the onset of the 2012 rainy season, movement was identified on the slope monitoring system and cracks developed on the slope. After a minor failure on the crusher slope an assessment of the slope stability was conducted and a slope management plan recommended, which included deployment of real-time monitoring. An evaluation of the conditions leading to instability was conducted and the likely causes for the failure identified. A full evaluation of the slope monitoring, rainfall, and mining conditions was undertaken and movement triggers were determined. This paper describes the events leading to the development of the failure and the evaluation of the monitoring data to determine a management plan for the failure that allowed for minimal shutdowns of the primary crusher.